2018
DOI: 10.1002/jcb.28213
|View full text |Cite
|
Sign up to set email alerts
|

RhoB antibody alters retinal vascularization in models of murine retinopathy

Abstract: Neovascularization in cancer or retinopathy is driven by pathological changes that foster abnormal sprouting of endothelial cells. Mouse genetic studies indicate that the stress-induced small GTPase RhoB is dispensable for normal physiology but required for pathogenic angiogenesis. In diabetic retinopathy, retinopathy of prematurity (ROP) or age-related wet macular degeneration (AMD), progressive pathologic anatomic changes and ischemia foster neovascularization are characterized by abnormal sprouting of endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A recent study has shown that hypoxia significantly upregulates the expression of RHOB (Huang et al, 2017). Concurrent studies suggested that RHOB was genetically required for pathogenic retinal angiogenesis (Almonte-Baldonado et al, 2019). Likewise, RHOB was also up-regulated in AAK patients.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study has shown that hypoxia significantly upregulates the expression of RHOB (Huang et al, 2017). Concurrent studies suggested that RHOB was genetically required for pathogenic retinal angiogenesis (Almonte-Baldonado et al, 2019). Likewise, RHOB was also up-regulated in AAK patients.…”
Section: Discussionmentioning
confidence: 97%
“…Increased RhoB transcription is associated with the disruptive effects of celiac patient antibodies on angiogenesis [83] and RhoB-null mice have decreased pathological angiogenesis in the ischemic retina, suggesting an important role in disease-specific angiogenesis [46] (Figure 4). Excitingly, an antibody against RhoB decreases angiogenesis in a model of proliferative retina angiogenesis and oxygen-induced retinopathy in an early pre-clinical study, suggesting that RhoB may not be required for vessel maintenance and could be specific to pathogenic vessels [84]. RhoB could represent an exciting new target for disease treatment in which blockage of abnormal angiogenesis, rather than angiogenesis as a whole, is desirable.…”
Section: Angiogenesismentioning
confidence: 99%